Does postexercise modelled capillary blood flow accurately reflect cardiovascular effects by different exercise intensities?. (26th April 2017) - Stöcker, F.; Von Oldershausen, C.; Paternoster, F. K.; Schulz, T.; Oberhoffer, R.
Summary: Blood flow (BF) in exercising muscles is an important factor for exercise capacity. Recently, a non‐invasive method to estimate capillary BF ( Q cap ) was introduced. Using this method, the Fick principle is re‐arranged by using relative differences in deoxygenated haemoglobin (ΔHHb) as a surrogate for arteriovenous O2 difference and pulmonary oxygen uptake (VO2 ) instead of muscular oxygen uptake. The aim of this study was to examine (I) the relationship between Q cap and exercise intensity during and following exercise, and (II) to critically reflect the Q cap approach. Seventeen male subjects completed six bouts of cycling exercise with different exercise intensities (40–90% peak oxygen uptake, VO2peak ) in randomized order. VO2 and ΔHHb were monitored continuously during the trail. Q cap was modelled bi‐exponentially, and mean response time (MRT) was calculated during recovery as well as the dissociation of modelled VO2 and Q cap recovery kinetics (MRT/τVO2 ). End‐exercise Q cap increased continuously with exercise intensity. This also applied to MRT. Postexercise MRT/τVO2 increased from 40 to 60% VO2peak but remained stable thereafter. The results show that Q cap response to exercise is linearly related to exercise intensity. This is presumably due to vasoactive factors like shear‐stress or endothelial‐mediated vasodilation. MRT/τVO2 shows that postexercise Q cap is elevated for a longer period than VO2, which is representative for metabolic demand following exercise ≥70% VO2peak . This is a hint for prolonged local vasodilation. According to previous studies, Q cap could not be modelled properly in some cases, which is a limitation to the method and therefore has to be interpreted with caution.